Development of an energy management system for an inhouse parallel hybrid electric vehicle - Pin, Banchaa Inthaknu (2012)
Environmental as well as economic issues provide a compelling impetus to develop clean, efficient, and sustainable vehicles for urban transportation. Automobiles constitute an integral part of our everyday life, yet the exhaust emissions of conventional internal combustion engines (ICE) vehicles are to be blamed for the major source of urban pollution that causes the greenhouse effect leading to global warming. One of the ways to overcome this problem is the hybrid electric vehicle. The hybrid electric vehicle serves as a compromise for the environmental pollution problem and the limited range capability of today’s purely electric vehicle. Hybrid electric vehicles have an electric motor as well as an internal combustion engine (ICE) to provide extended range and to ease down the pollution problem. The purpose of this study is to develop and model the energy management system of two energy sources in a hybrid electric vehicle which are the internal combustion engine and the electric motor. A small scale of a hybrid electric vehicle is constructed from a 1/10th size of a nitro-engine remote control car coupled with an electric motor. The energy management system is then developed by using microcontrollers and the power division between the two energy sources is controlled by the state of charge of the motor’s battery. At the end of this project, the rpm of the motor is managed to be dependent on the state of charge of the battery and the lower the percentage of the battery state of charge, the lower the rpm of the electric motor and the higher the rpm of the engine, and vice versa.